Heavy alcohol consumption but not smoking predicts mortality in patients with acute coronary syndrome - Allan Andersen; Steven R. H. Beach; Willem Philibert; James A. Mills; Emily Milefchik; Emma Papworth; Kelsey Dawes; Joanna Moody; Gracie Weeks; Ellyse Froehlich; Kaitlyn deBlois; Jeffrey D. Long; et al. (Epigenetics)
The relationship of heavy alcohol consumption (HAC) and smoking to mortality in those with CHD, and mechanisms through which these effects are elicited are not clear. In order to improve our understanding, we examined the relationship of Alcohol T-Scores (ATS), an epigenetic biomarker of chronic HAC, and cg05575921 methylation, a biomarker of smoking intensity, with all-cause mortality and degree of coronary artery obstruction in a cohort of 217 subjects admitted for CHD-related acute coronary syndrome (ACS). We found that 65% of the subjects had ATS values indicative of chronic HAC. ATS values, but not cg05575921 values, were significantly associated (p < 0.02) with subsequent proband death (total of 28 deaths) with a Cox Proportional Hazards model showing a slightly larger effect of ATS levels than age on all-cause mortality survival (overall model, p < 0.003). Subjects in the highest decile of ATS scores had a 2.4-fold increase in the risk for mortality as compared to those in the lowest decile. In contrast, cg05575921 methylation (p < 0.003) but not ATS scores, were significantly inversely associated with degree of obstruction. Only 2 of the 217 subjects were referred for treatment for either smoking or drinking. We conclude that HAC is an underappreciated driver of CHD-related mortality, that those with ACS who smoke are much less likely to have significant obstruction upon cardiac imaging and that substance use treatment may be underutilized in those with CHD.